Low Lactose Milk Production of Soybean by Fermentation Technique Using Rhizopus oligosporus - Farid Salahudin; Hidayati Hidayati (Biopropal Industri, 2013)
Milk is an important food for baby that contains lactose. Normally, a baby could produce lactase enzyme that digest lactose, but in the diarrhea case lactose could not be digested. So, Low Lactose Milk is needed. Low Lactose Milk usually produced from rice or almonds that have low protein. Soybean (Glycine max) is the commodity with rich of protein and also contains raffinose and stachyose, which can lead flatulence. Raffinose and stachyose could be reduced by Rhizopus oryzae at tempe process from lamtoro beans.  So the aim in this research is to know the optimum time of soybean fermentation with R. oryzae to reduce stachyiose  and raffinose. The research was done with innoculation of R. oryzae isolate in the soybeans fermentation for 72 hours. N index, raffinose and stachyose level was tested. The result shows that optimum fermentation time is 48 hour and using 5% skim milk as filler.